A COMPARISON OF ESTIMATED LIFE OF KNEE IMPLANT APPLYING THE MULTIAXIAL FATIGUE CRITERIA - Kashani, H Moayeri; Zolfaghari, A (MATTER: International Journal of Science and Technology, 2018)
The experience of losing a part of body is very painful and irritating, many factors, such as sports injuries, arthro-rheumatoid arthritis, weight gain, car accidents, and the like can sometimes lead to the destruction of joints and knee tissues. Today the most successful and fastest process to assist these people is the introduction of total knee replacement. Therefore, the evaluation of the materials used and the life estimation of knee implants used in total knee replacement are of particular importance. This article investigates the stress analysis and life estimation of knee implants in multiaxial loading. For this purpose, the tibia and femur were modeled using the results of the CT scan of a completely normal sample, and using the Solidworks software, followed by modelling implant sections and other sets. The analysis of stress and application of problem conditions were done in Abaqus finite element analysis software and life estimation was done using coding in MATLAB software. Based on the walking cycle, the minimum load of 200 N and maximum of 2600 N was applied to metatarsus in standing position, and finally, using stress analysis and multiaxial fatigue criteria such as Von Mises, the maximum principal stresses, maximum shear stress (Tresca), maximum principal strain, Brown Miller, Fatemi-Socie and Smith Watson Topper, the life of the implant was estimated and the results were compared. Ultimately, the longest life expectancy was estimated on the basis of the Tresca criterion and the shortest life span on the basis of the Smith Watson-Topper criteria.